An Electrochemical Gelation Method for Patterning Conductive PEDOT:PSS Hydrogels. Issue 39 (15th August 2019) - Feig, Vivian Rachel; Tran, Helen; Lee, Minah; Liu, Kathy; Huang, Zhuojun; Beker, Levent; Mackanic, David G.; Bao, Zhenan
Abstract: Due to their high water content and macroscopic connectivity, hydrogels made from the conducting polymer PEDOT:PSS are a promising platform from which to fabricate a wide range of porous conductive materials that are increasingly of interest in applications as varied as bioelectronics, regenerative medicine, and energy storage. Despite the promising properties of PEDOT:PSS‐based porous materials, the ability to pattern PEDOT:PSS hydrogels is still required to enable their integration with multifunctional and multichannel electronic devices. In this work, a novel electrochemical gelation ("electrogelation") method is presented for rapidly patterning PEDOT:PSS hydrogels on any conductive template, including curved and 3D surfaces. High spatial resolution is achieved through use of a sacrificial metal layer to generate the hydrogel pattern, thereby enabling high‐performance conducting hydrogels and aerogels with desirable material properties to be introduced into increasingly complex device architectures. Abstract : PEDOT:PSS hydrogels are an important framework for creating conductive porous materials that are of broad interest to researchers in the fields of bioelectronics, tissue engineering, stretchable electronics, and energy. To incorporate these materials into devices, a novel patterning method is presented that uses electrochemically produced ions to rapidly generate PEDOT:PSS hydrogel patterns with high spatial resolution.